2021
DOI: 10.3389/fpsyg.2021.731929
|View full text |Cite
|
Sign up to set email alerts
|

School Principals’ Stress Profiles During COVID-19, Demands, and Resources

Abstract: The present study examined latent profiles of school principals’ stress concerning students’, teachers’, parents’, and principals’ own ability to cope during the COVID-19 pandemic. In addition, the role of job demands (workload, remote work stress, difficulty to detach from work, COVID-19 crisis, COVID-19 infections at school, impact of COVID-19 on future teaching), resources (buoyancy, effective crisis leadership, social appreciation, successful transition to remote teaching), and occupational well-being (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 49 publications
3
21
0
Order By: Relevance
“…Principals also recognized the vital role of wider community networks in providing the necessary support and resources to address the crisis effectively (Thornton, 2021). As a type of support, social appreciation was significantly associated with low stress levels among principals during the pandemic (Upadyaya et al, 2021). Studies have also noted that the direction of effects on principal well-being greatly depends on their types of support (Beausaert et al, 2016), leaving space for future research to study the effects of work-related support on their well-being.…”
Section: Professional Support and Compassion Fatigue Among Principalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Principals also recognized the vital role of wider community networks in providing the necessary support and resources to address the crisis effectively (Thornton, 2021). As a type of support, social appreciation was significantly associated with low stress levels among principals during the pandemic (Upadyaya et al, 2021). Studies have also noted that the direction of effects on principal well-being greatly depends on their types of support (Beausaert et al, 2016), leaving space for future research to study the effects of work-related support on their well-being.…”
Section: Professional Support and Compassion Fatigue Among Principalsmentioning
confidence: 99%
“…In August 2020, a poll revealed that 45% of principals were considering expediting their departure from the profession due to the pandemic's challenging working conditions (Havens, 2020). Upadyaya et al (2021) indicated that 77% of school principals reported that their high stress levels were related to their school community's ability to manage the pandemic crisis. Many principals turned to their personal and professional networks to manage their stress (DeMatthews et al, 2021), while school psychologists offered more consultation services to assist school leadership during the pandemic (Reupert et al, 2022).…”
mentioning
confidence: 99%
“…In a school principal's job, workload is a typical demand, which is characterized by completing multiple tasks, and requires extended effort. In addition, the following job demands are also important: role conflict, task and policy ambiguity (Devos et al, 2018;Elomaa et al, 2021;Upadyaya et al, 2021). In this regard, it is interesting to analyze whether the COVID-19 pandemic is characterized by these job demands and to what degree this is related to school principals' feelings of burnout.…”
Section: Job Demands and Job Resources Among School Principalsmentioning
confidence: 99%
“…Also, job resources refer to physical, psychological, social or organizational aspects of the job that are functional in achieving work goals, reduce job demands and the associated physiological and psychological costs and stimulate personal growth, learning and development (Demerouti et al, 2001). Research indicates that the following job resources are important for school principals: strong work relationships, autonomy and skill utilization (Devos et al, 2018;Elomaa et al, 2021;Upadyaya et al, 2021). As for the job demands, it is useful to analyze if the pandemic influences school principals' job resources and consequently is related to burnout.…”
Section: Job Demands and Job Resources Among School Principalsmentioning
confidence: 99%
“…During the pandemic, school principals’ responsibilities have changed unexpectedly and considerably. They are expected to be dynamic and flexible in allocating resources and finances, complying with infection prevention guidelines, and motivating and collaborating with teachers and students to ensure learning and teaching activities, even in a virtual environment [ 15 ]. The extra work and burden placed school leaders under enormous pressure, which may cause burnout, stress and other mental health problems [ 11 ].…”
Section: Introductionmentioning
confidence: 99%